Peningkatan Kemampuan Membaca Permulaan melalui Media Flash Card pada Siswa Kelas 1 SD di biMBA-Aiueo Kramat Semanan - Annissa Chaerani; Ahmad Arif Fadilah; Arry Patriasurya Azhar; Ina Magdalena; Sa’odah Sa’odah (Departement of Mathematics Education, 2023)
This thesis is motivated by the low development of early reading skills in grade 1 elementary school students at biMBA-AIUEO Kramat Semanan. This study also aims to improve early reading skills using flash card media in pre-school age children. The subject of this study consisted of 13 children, 8 boys and 5 girls. This research is a classroom action research that uses the Kemmis and Mc Taggart research model while the data collection techniques used by observation, interviews, documentation and tests. The data analysis technique using quantitative descriptive percentage. The results shows that the early reading ability of children at biMBA-AIUEO Kramat Semanan improved gradually by using flash card media through the steps, namely, recognizing the relationship of letters to sounds, distinguishing letters/recognizing familiar letters, mentioning words with the same initial letters, combining syllables into words, mentioning pictures that have words, and reading words clearly. The improvement can be proven from the result of the first cycle research is in the criteria of developing as expected by 53%, then increase in cycle II to 80%, and increasing to 96.3% in the third cycle. From the description above, it can be concluded that using flash card media can improve early reading skills in pre-school age children at biMBA-AIUEO Kramat Semanan, Kalideres District, West Jakarta.